COVID-19 Detection by Salivary Analysis: Easy and Reliable Approach in Massive Outbreak - Mojumder, Dipayan; Paul, Satabdi; Banik, Ruman; Ferdushi, Hasina Mahmuda (International Journal of Human and Health Sciences (IJHHS), 2020)
Coronavirus disease (COVID-19) caused by 2019 Novel Coronavirus (2019-nCoV) recently emerged from Wuhan, Hubei province, China in December 2019. It showed devastating nature and already involved almost all the territories all over the world. It is a contagious disease and rapid, reliable diagnosis is needed to take measure for decreasing the infection rate. For detection of COVID-19 nasopharyngeal swab, sputum, bronchoalveolar lavage, saliva and other body fluid identified as useful samples. The aim of this review from recent studies is to explore the possibility of salivary analysis to identify COVID-19. Although nasopharyngeal swab is taken for rRT-PCR test as a worldwide accepted method, but it is a technique sensitive procedure needs expert personnel and adequate protection is necessary to avoid contamination. In the contrary, saliva sample can be taken easily by the patient himself at home which is a low-risk procedure and economical. So, in the pandemic of COVID-19, salivary analysis could be a good option for detection. Future study on this might explore the possible diagnostic capability of saliva for different diseases and underlying mechanism to find out the pathway for targeted drug therapies. International Journal of Human and Health Sciences Vol. 05 No. 01 January’21 Page: 7-11